Post-harvest seaweed quality support in Pagarbatu Village, Sumenep, using SWSolar Dryer technology to create competitive seaweed farmers - Zuhri, Ach; Ahsan, Agung Firdausi; Saadah, Siti; Ghibran, Moh Iqbal; Aini, Anis Nur (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
Seaweed is a leading commodity in Sumenep Regency. However, post-harvest quality remains low due to traditional drying methods, which, in turn, affects selling prices and farmer welfare. This community service program aims to improve the quality and competitiveness of seaweed farmers in Pagarbatu Village by applying SW-Solar Dryer technology. Implementation methods include outreach, management and production training, SW-Solar Dryer application, mentoring, and ongoing evaluation with